Information systems security and privacy : third International Conference, ICISSP 2017, Porto, Portugal, February 19-21, 2017, Revised selected papers /: third International Conference, ICISSP 2017, Porto, Portugal, February 19-21, 2017, Revised selected papers. (2018) - Unknown
No abstract available